Ebola in West Africa - Raka, Lul (Open Access Maced J Med Sci, 2015)
Ebola viral disease (EVD) is a severe and life-threatening disease. The current Ebola outbreak in West Africa entered its second year and is unprecedented because it is the largest one in history, involved urban centers and affected a large number of health care workers. It quickly escalated from medical into a humanitarian, social, economic, and security crisis. The primary pillars to prevent EVD are: early diagnosis, isolation of patients, contact tracing and monitoring, safe burials, infection prevention and control and social mobilization. The implementation of all these components was challenged in the field. Key lessons from this Ebola outbreak are that countries with weak health care systems can’t withstand the major outbreaks; preparedness to treat the first confirmed cases is a national emergency; all control measures must be coordinated together and community engagement is the great factor to combat this disease.